The effectiveness of curfew on teenagers based on parents point of view / Nur Farhani Alidin and Shirley Vanessa Sebastian - Alidin, Nur Farhani; Sebastian, Shirley Vanessa (2017)
Environment nowadays a more dangerous especially for teenagers since they tend to exposed with many wrongdoing and crimes. We can see it by looking at the case that involved teenagers who are actually still need to be monitor by their family which is parents, the one who must take responsibility towards their children. Teenagers' crime or wrongdoing usually happened at night. They tend to go out at night bedause of they want to feel the freedom as adult where they are not yet need to feel that way according to their age. They are too young to think about what is wrong and which is right. They usually follow they own passion to be in the group that they like. To avoid this to be happen parents put a curfew for them to make sure they did not join any bad activities especially those street people. Parents putting this as a solution so that teenagers can spend more time at home doing activities that more relevant as children such as spending time with family or do any others good activities for example school homework and so on. To keep them in track with good time management and so on.